APPLICATION OF CONTENTS NORMALIZED DIFFERENCE VEGETATION INDEX (NDVI) IN PICTURES CBERS 2B IN BOTUCATU-SP - RODRIGUES, Mikael T.; RODRIGUES, Bruno T. (Revista Brasileira de Engenharia de Biossistemas, 2012)
The purpose of this article was to test the application of vegetation index NDVI satellite images CBERS 2B CCD sensor in the whole area of Botucatu - SP. The images are dated 07/12/2008, bands 3 and 4 which correspond to bands of visible red, near infrared, being respectively used. Such bands are often used in categorization of satellite imagery analysis for agricultural and environmental studies. The vegetation index NDVI (Normalized Difference Vegetation Index) is the indicator most used lately, partially reduce the effect of topography, and present a linear measurement range between -1 and 1, where the zero value are designated as a set of pixel absence of vegetation (Ramos et. al., 2010). The NDVI portrayed the condition and the degree of degradation suffered on the surface of Botucatu, abeam the removal of vegetation cover mainly the edges of the urban area and in the northern sector, presenting targets with values between 0.10 and 0.30.